Struktur Naskah Radio Citra Ayu Senada (CAS) FM - Winda Kustiawan; Chaerona Artha Lubis; Lola Fahira; Muhammad Fauzan Fayrozi (Universitas Muhammadiyah Enrekang, 2022)
Good Corporate Governance is very important for the industry to protect the interest of investors and policyholders. The crisis of public confidence illustrates the existence of doubt about the governance of insurance company. Complaints about cases related to the insurance industry are still often heard today. The share of the Islamic non-bank financial market is still below 5 percent when compared to conventional. The poor implementation of good corporate governance (GCG) is the culprit. By using a literature study, this research aims to analyze the importance of advancing the insurance industry by implementing a good corporate governance system. The results of the study show that it is true that in general cases of default and other complaints related to insurance are caused by the only management of the governance system at the insurance company so that it affects actions the violate the principle of good corporate governance, namely deviating from the provisions of the TARIF (Transparancy, Accountable, Responsibelty, Indenpendency, Fairness).